2004
DOI: 10.1063/1.1795111
|View full text |Cite
|
Sign up to set email alerts
|

Time resolved laser-induced fluorescence of electrosprayed ions confined in a linear quadrupole trap

Abstract: We have designed and constructed a linear quadrupole ion trap for the measurement of laser-induced fluorescence (LIF) of mass selected gas-phase ions produced by electrospray ionization. The instrument consists of a simple electrospray source, radiofrequency octopole guide, a dc quadrupole bender, a quadrupole mass filter, the linear quadrupole trap (which is equipped with optics for LIF collection and a channeltron ion detector), and several multielement focusing lenses. With this instrument, the LIF decay li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Isolation of a particular m/z inside the ion trap ensures that both the charge state of the sample is known and, importantly, that contaminants are removed from the ion population under investigation. Several laboratories have implemented fluorescence excitation and detection capabilities into trapping mass spectrometry set-ups in order to individually probe mass-selected populations of large ions formed by ESI or MALDI using laser-induced fluorescence emission [28][29][30][31][32][33][34][35] as well as fluorescence lifetime measurements [36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Isolation of a particular m/z inside the ion trap ensures that both the charge state of the sample is known and, importantly, that contaminants are removed from the ion population under investigation. Several laboratories have implemented fluorescence excitation and detection capabilities into trapping mass spectrometry set-ups in order to individually probe mass-selected populations of large ions formed by ESI or MALDI using laser-induced fluorescence emission [28][29][30][31][32][33][34][35] as well as fluorescence lifetime measurements [36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group [1][2][3][4] and several others [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] have presented works focusing upon the development, characterization and applications of instrumentation for measuring laser-induced fluorescence from molecular ions in the gas phase. The majority of these studies have used highly fluorescent molecules such as the xanthene-based rhodamine dyes.…”
Section: Introductionmentioning
confidence: 99%
“…The instrumentation developed features laser light sources coupled into trapping mass spectrometers that are used to mass-select the ion population of interest and to store the selected ion population for extended periods of time. Several types of mass spectrometers have been employed, including 3-D Paul-type quadrupole ion traps (QIT) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], Fourier transform ion cyclotron resonance mass spectrometers (FT-ICR-MS) [18][19][20][21][22][23], and linear radiofrequency ion traps (LIT) [24]. Detection of integrated gas-phase fluorescence has been accomplished using high-sensitivity photomultiplier tubes [5-7, 9-11, 13-17, 21-24] or avalanche photodiodes [18,19,25], while dispersed fluorescence has been measured using spectrographs with charge-coupled device (CCD) detectors [1-4, 8, 12, 22].…”
Section: Introductionmentioning
confidence: 99%
“…In principle, optical spectroscopic investigations thereby can be combined with any of the mass spectrometric methods described previously [9,10]. Marshall et al have measured laser-induced fluorescence (LIF) excitation and emission spectra as well as LIF lifetimes of ions trapped in a Fourier transform ion cyclotron resonance (FTICR) cell [11][12][13]. Scott et al showed a dual cell setup for obtaining fluorescence lifetimes of trapped ions [14].…”
mentioning
confidence: 99%